The HIF‐1α/p53/miRNA‐34a/Klotho axis in retinal pigment epithelial cells promotes subretinal fibrosis and exacerbates choroidal neovascularization - Xie, Laiqing (J Cell Mol Med, 2021)
Wet age‐related macular degeneration (wAMD), characterized by choroidal neovascularization (CNV), is a leading cause of irreversible vision loss among elderly people in developed nations. Subretinal fibrosis, mediated by epithelial‐mesenchymal transition (EMT) of retinal pigment epithelium (RPE) cells, leads to unsuccessful anti‐vascular endothelial growth factor (VEGF) agent treatments in CNV patients. Under hypoxic conditions, hypoxia‐inducible factor‐1α (HIF‐1α) increases the stability and activation of p53, which activates microRNA‐34a (miRNA‐34a) transcription to promote fibrosis. Additionally, Klotho is a target gene of miRNA‐34a that inhibits fibrosis. This study aimed to explore the role of the HIF‐1α/p53/miRNA‐34a/Klotho axis in subretinal fibrosis and CNV. Hypoxia‐induced HIF‐1α promoted p53 stability, phosphorylation and nuclear translocation in ARPE‐19 cells (a human RPE cell line). HIF‐1α‐dependent p53 activation up‐regulated miRNA‐34a expression in ARPE‐19 cells following hypoxia. Moreover, hypoxia‐induced p53‐dependent miRNA‐34a inhibited the expression of Klotho in ARPE‐19 cells. Additionally, the HIF‐1α/p53/miRNA‐34a/Klotho axis facilitated hypoxia‐induced EMT in ARPE‐19 cells. In vivo, blockade of the HIF‐1α/p53/miRNA‐34a/Klotho axis alleviated the formation of mouse laser‐induced CNV and subretinal fibrosis. In short, the HIF‐1α/p53/miRNA‐34a/Klotho axis in RPE cells promoted subretinal fibrosis, thus aggravating the formation of CNV.